2011
DOI: 10.1111/j.1365-294x.2011.05138.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of the plant pathogenic fungus Melampsora larici-populina on its wild host is extensively impacted by host domestication

Abstract: Wild and cultivated plants represent very different habitats for pathogens, especially when cultivated plants bear qualitative resistance genes. Here, we investigated to what extent the population genetic structure of a plant pathogenic fungus collected on its wild host can be impacted by the deployment of resistant cultivars. We studied one of the main poplar diseases, poplar rust, caused by the fungus Melampsora larici-populina. A thousand and fifty individuals sampled from several locations in France were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 84 publications
8
87
0
3
Order By: Relevance
“…Conversely, the sexual stage of this rust fungus occurs on larch needles (Larix sp.) in spring (Xhaard et al 2011), persisting for a long time from the vegetative stage to the sexual stage. Additional work is required to explore the function of the MlpHog1 gene during the sexual stage.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the sexual stage of this rust fungus occurs on larch needles (Larix sp.) in spring (Xhaard et al 2011), persisting for a long time from the vegetative stage to the sexual stage. Additional work is required to explore the function of the MlpHog1 gene during the sexual stage.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis to account for this subclade is that it represents a newly evolved taxon, derived from M. epitea, which is specifically adapted to S. lapponum, S. myrsinites, and their hybrids and therefore has high virulence on them. Such a new taxon may have a lower diversity than the taxon from which it has been derived because it has passed through a bottleneck during the process of adapting to the restricted set of hosts (Xhaard et al 2011). This hypothesis predicts that infection levels on S. lanata, and the Salix species to which the subclade is adapted, should be decoupled.…”
mentioning
confidence: 96%
“…Pinon & Frey (1997) reported the main selection force exerted on rust populations was host population. However, Xhaard et al (2011) showed poplar cultivation influenced spatial distribution and genetic structure of the fungal plant pathogen and resulted in the spread of a range of different virulence alleles in most pathogen populations.…”
Section: Introductionmentioning
confidence: 99%